A comparative study of pH modulation and trace elements of various fruit juices on enamel erosion: An in vitro study - S.V.S.G Nirmala; V V Subba Reddy (Wolters Kluwer Medknow Publications, 2011)
Fruit juices are popular worldwide with children of all ages as they are sweet and perceived to be healthful. This in vitro study was sought to measure pH of 10 different fruit juices, to find out possible erosive effects on human dental enamel of 40 extracted sound premolars and also to measure fluoride and trace elements of these juices. The estimation of pH of fruit juices was done by using Systronic upH 362 pH meter. The erosive effects of fruit juices were tested by using polarized light microscope. Orion electrode was used to measure fluoride. The trace elements were estimated by using Atomic Absorption Spectrophotometer No. 6501F. The pH values in different juices were observed at different levels, and pH values of these juices were more acidic than baseline after 24 hours. As the time increased, the erosion effect became more in pineapple; grape and sugarcane juices, and they had more cariogenic trace elements like selenium, iron and manganese. So, these juices were found to be cariogenic. To conclude, orange, mousambi, mango, pomegranate, apple, chikku and watermelon juices had no erosive effect on the human enamel, with the presence of highest amount of trace elements like fluoride and phosphorous which are considered as strongly cariostatic.